Distance learning in mathematics with teams and SIACUA - Carvalho, P. (2021)
The need for distance teaching and assessment due do Covid-19, was a great opportunity to apply and improve the computer systems and digital contents for autonomous learning we have been developing in the previous years. We describe an experience using a teaching methodology that combines the well-known MS Teams with a computer system we have been developing, named SIACUA. SIACUA aims to simulate one-to-one teaching and it has been proven to be effective as a complement to face-to-face teaching. It aims to provide the simplest possible interface for individual autonomous learning, with a course index with progress bars and, for each entry in that index, a learning object (LO) to recall relevant previous concepts, a LO for introduction, references for a complete study and finally, the possibility to answer many parameterized questions, with a Bayesian system to compute and provide feedback. This system was used in distance learning to provide best possible conditions to present the materials for the asynchronous part of distance teaching. MS Teams was used for the synchronous part of teaching, for short distance classes, and for collaboration, with a strategy using many assessment-for-learning elements along the semester. Group works have been set in a way that motivated students to help each other, using MS Teams. The same methodology has been used in two different calculus courses for sciences and engineering, Calculus 1, for the first year, with 49 students, and Calculus 3, for the second year, with 33 students. We present this experience, including data from activity along the semester, together with results from informal surveys. Although the methodology and teacher were the same, the results were significantly better for second year students. We discuss several aspects of methodology design for distance and blended learning and the need to adapt it considering student maturity among other elements.